Topography of genetic elements of X-chromosome relative to the cell nucleus and to the chromosome X territory determined for human lymphocytes - Falk, Martin; Lukásová, Emilie; Kozubek, Stanislav; Kozubek, Michal (Gene, 2002)
Topography of three genetic elements--dystrophin (dmd) exons 5-7 (E(1)), 46-47 (E(2)), and centromere of chromosome X (N(X)) were studied relative to cell nuclei and to chromosome X territories of spatially fixed human lymphocytes. Repeated three-dimensional (3D) dual color fluorescence in situ hybridization combined with high-resolution cytometry was used. In addition, the nuclear location of fluorescence weight centers (FWC), spatial volume, and maximal area per one section of chromosome-X territories were investigated. The larger (X(L)) and smaller (X(S)) homologous X-chromosomes were distinguished for each nucleus according to the 3D volume of their territories. The distributions of the [center of nucleus]-to-[genetic element] distances (radial distributions) of dmd exons E(1), E(2), centromere N(X) and FWC were very similar for both homologous X-chromosomes of female lymphocytes as well as for the chromosome X of the human male. On the other hand, larger average mutual distances between all pairs of signals (E(1), E(2), N(X), FWC) and larger average maximal area were observed for the larger chromosome (X(L)) in comparison with the smaller one (X(S)). The territory of the larger homologue showed also more irregular surface. The most significant differences between homologous X-chromosomes were found for N(X)-E(1), N(X)-E(2) and E(1)-E(2) distances that were in average about twice longer for X(L) as compared with X(S). These parameters correlate to each other and can be used for the reliable determination of more (de)condensed X-chromosome territory. The longer E(1)-E(2) distances for X(L) indicate more open chromatin structure of the dystrophin gene on this chromosome in contrary to closed structure on X(S). Substantially shorter distances of the dystrophin exons from the centromeric heterochromatin in X(S) as compared to X(L) can be explained by silencing effect of centromeres as described in Nature 1 (2000) 137.
Keywords: centromera; In Situ Hybridization, Fluorescence; Image Processing, Computer-Assisted; kultivované buňky; Humans; hybridizace in situ fluorescenční; Centromere; lymfocyty; buněčné jádro; Cell Nucleus; Lymphocytes; Dystrophin; Cells, Cultured; fluorescenční mikroskopie; chromozom X; X Chromosome; Microscopy, Fluorescence; lidé; počítačové zpracování obrazu; dystrofin